Functional and expressional analyses of apple FLC-like in relation to dormancy progress and flower bud development. (14th November 2019) - Nishiyama, Soichiro; Matsushita, Miwako Cecile; Yamane, Hisayo; Honda, Chikako; Okada, Kazuma; Tamada, Yosuke; Moriya, Shigeki; Tao, Ryutaro
Abstract: We previously identified the FLOWERING LOCUS C ( FLC ) - like gene, a MADS-box transcription factor gene that belongs to Arabidopsis thaliana L. FLC clade, in apple ( Malu s $×$ domestica Borkh. ), and its expression in dormant flower buds is positively correlated with cumulative cold exposure. To elucidate the role of the MdFLC- like in the dormancy process and flower development, we first characterized the phenotypes of MdFLC- like overexpressing lines with the Arabidopsis Columbia-0 background. The overexpression of MdFLC- like significantly delayed the bolting date and reduced the plant size, but it did not significantly affect the number of rosette leaves or flower organ formation. Thus, MdFLC- like may affect vegetative growth and development rather than flowering when expressed in Arabidopsis, which is not like Arabidopsis FLC that affects development of flowering. We compared seasonal expression patterns of MdFLC- like in low-chill 'Anna' and high-chill 'Fuji' and 'Tsugaru' apples collected from trees grown in a cold winter region in temperate zone and found an earlier upregulation in 'Anna' compared with 'Fuji' and 'Tsugaru'. Expression patterns were also compared in relation to developmental changes in the flower primordia during the chilling accumulation period. Overall, MdFLC- like was progressively upregulated during flower primordia differentiation and development in autumn to early winter and reached a maximum expression level at around the same time as the genotype-dependent chilling requirements were fulfilled in high-chill cultivars. Thus, we hypothesize MdFLC- like may be upregulated in response to cold exposure and flower primordia development during the progress of endodormancy. Our study also suggests MdFLC- like may have a growth-inhibiting function during the end of endodormancy and ecodormancy when the temperature is low and unfavorable for rapid bud outgrowth.